2020
DOI: 10.1111/aos.14442
|View full text |Cite
|
Sign up to set email alerts
|

Autologous neurosensory retinal transplantation for recurrent macular hole retinal detachment in highly myopic eyes

Abstract: Purpose To investigate the morphological and functional reconstruction of the macular fovea after autologous neurosensory retinal transplantation for recurrent macular hole retinal detachment (MHRD) in highly myopic eyes. Methods Ten consecutive cases of recurrent MHRD with high myopia were retrospectively reviewed. All eyes underwent pars plana vitrectomy combined with autologous neurosensory retinal transplantation and were followed up for at least 3 months after silicone oil extraction. The main outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…However, we have not yet carried out these technologies for legal reasons. In this study, we had five eyes that underwent ANRT and SO refilling surgery, and 80% of cases (4/5) were finally anatomically reattached successfully (RD reattachment and MH closure), which is consistent with that in our previous report 39 . Recently, an international multicenter study also reported that ANRT could obtain a high reclosure rate of 87.8% in the treatment of an unclosed high-myopia MH after PPV combined with ILM peeling 40 .…”
Section: Discussionsupporting
confidence: 88%
“…However, we have not yet carried out these technologies for legal reasons. In this study, we had five eyes that underwent ANRT and SO refilling surgery, and 80% of cases (4/5) were finally anatomically reattached successfully (RD reattachment and MH closure), which is consistent with that in our previous report 39 . Recently, an international multicenter study also reported that ANRT could obtain a high reclosure rate of 87.8% in the treatment of an unclosed high-myopia MH after PPV combined with ILM peeling 40 .…”
Section: Discussionsupporting
confidence: 88%
“…Some scholars have studied autologous or allogenic lens capsular flap transplantation 4 , autologous neurosensory retinal free flap (ANRFF) transplantation 5 and other techniques for use in patients with recurrent macular holes. However, the above techniques are still associated with certain trauma and technical difficulty, and "the losses outweigh the gains".…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrent macular holes have often undergone pars plana vitrectomy (PPV) more than once. Therefore, the macular area in these patients may not have an adequate inner limiting membrane 3 5 . This means that the reoperations may be extremely difficult, and the results may be poor.…”
Section: Introductionmentioning
confidence: 99%
“…10,30 Anatomic, Visual, and Functional Outcomes When analyzing ART series of at least five eyes, the weighted mean closure rate was 88% (range: 66.7%-100%) for a variety of MH repairs (Table 1). 9,10,25,[28][29][30][31][32][33][34] Patients with larger MH diameters demonstrated lower rates of successful closure. 9,34 Cases without successful closure usually did not achieve graft integration into the surrounding tissue.…”
Section: Surgical Techniquementioning
confidence: 99%
“…9 Many patients gained several lines of visual acuity (Table 2). 9,10,25,[28][29][30][31][32][33][34] In the largest ART series, 12% of patients attained a postoperative visual acuity of 20/50 or better after ART for primary or refractory MH; none of these patients underwent ART for combined MH-retinal detachment. 28 Anatomic features associated with significant visual acuity improvement included ellipsoid zone reconstitution and alignment of neurosensory layers (ANLs) (graft inner plexiform layer to host inner plexiform layer, graft outer plexiform layer to host outer plexiform layer, etc.).…”
Section: Surgical Techniquementioning
confidence: 99%